THE ROLE OF FEAR OF MISSING OUT IN MEDIATING THE EFFECT OF TWIN DATE EVENT PROMOTION E-COMMERCE SHOPEE AGAINSTIMPULSIVE BUYING TENDENCY - Jumarni; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
This article aims to analyze the role of Fear of Missing Out (FoMO) in mediating the influence of the date twin’s promo event on Shopee e-commerce on impulsive buying tendencies. This study focuses on the phenomenon of increased impulsive buying triggered by limited promotions on e-commerce platforms and the fear of delays experienced by consumers. This study was conducted with a quantitative approach using literature studies from scientific journals and academic sources as well as other relevant research results. This shows that the date twins promo event on Shopee has a significant influence on consumers' impulsive buying tendencies. FoMO acts as a mediator that strengthens the relationship where consumers who experience FoMO tend to be more likely to make impulsive purchases due to urgency and exposure to limited offers. These findings provide important insights for e-commerce business actors to design effective marketing strategies by considering consumer psychological factors such as FoMO.